Front Cover: Parallel Screening with 14C‐Labeled Carbon Dioxide: De‐risking the Staudinger‐Aza‐Wittig Reaction (Eur. J. Org. Chem. 30/2022). Issue 30 (22nd July 2022) - Babin, Victor; Sallustrau, Antoine; Molins, Maxime; Labiche, Alexandre; Goudet, Amélie; Taran, Frédéric; Audisio, Davide
Abstract : The Front Cover illustrates how radiolabeling using 14C‐labeled CO2 was used to evaluate the robustness of the Staudinger‐Aza‐Wittig reaction, as a general methodology for the direct functionalization of CO2 . In the presence of various additives, it easily allowed for the identification of side reactions, leading to the preparation of thiocarbamates. Cover design by Antoine Sallustrau. More information can be found in the Research Article by Davide Audisio et al .